Pravne podlage za ureditev položaja infrastrukturnih omrežij na tujih zemljiščih - Damjan, Matija (Pravni letopis, 2013)
Public infrastructure networks in nature pass over a number of plots of land not owned by the network operators. In property law, such a relationship between the property owner and the facility operator is supposed to be regulated by establishing an easement or a superficies right. Construction law requires that the investor proves his right to build. However, the comparison between the data of public infrastructure cadastre and the land registry data shows that for most existing networks, the existence of such rights to build on others land is an exception rather than the rule. The disordered legal situation of public infrastructure can lead to conflicts, especially in relation to ducts installed underground, the course of which is not openly visible. The property owner and the network operator who acted in good faith, both have a legitimate interest in protecting their position; elements of public interest are also present. The article first seeks the legal basis for regularising public infrastructure networks on others land in the legislation that was relevant for the construction of networks in the (Yugoslav) social property period and later. Next, special provisions are examined that are contained for such purposes in the legislation on public utilities, telecommunications and energy sector.The instruments of expropriation and easement in the public interest are also addressed.
Keywords: infrastructure; infrastruktura; lastnina; služnostne pravice; stvarne služnosti; stvarno pravo; zemljišča